PERENCANAAN SETTING DIRECTIONAL GROUND RELAY (DGR) UNTUK GANGGUAN SATU FASA KE TANAH DI SALURAN 150 KV DOUBLE CIRCUIT GIS PESANGGARAN – GI NUSA DUA - Maulana Idham, Ganggas B; Dyana Arjana, I Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
The single phase to ground fault on the 150 kV transmission line GIS Pesanggaran – Nusa Dua Substation has a high fault impedance so that the distance relay as an auxiliary safety device cannot detect the disturbance. Directional Ground Relay (DGR) was chosen as an auxiliary protection relay to secure the system from single phase to ground faults. Installation of auxiliary protection relays requires planning and relay setting steps to obtain Iset, TMS and trip time. The calculations that have been carried out get the results of DGR setting with a pickup current range of 0.0522 – 0.0722 A. DGR will work after 2.297 seconds if the differential relay as the main protection relay does not work or fails and the distance relay as a backup protection does not succeed in securing a single phase fault to ground as well.